Identification of tourist area from remotely sensed data. - Hassan, Azmi; Mansor, Shattri (1989)
Using technology developed for satellite image processing,identification of future tourist area to be developed can be easily accomplished. Remotely sensed data from satellite such as LANDSAT MSS and SPOT1 are used in the study. A software using a microcomputer has been developed. Case study of Southern Johor is presented. Results are summarised and compiled in terms of map which have been identified,classified and coded into symbols.